Rural Women's Economic Empowerment in Africa: Research Frontiers and Operational Action - Reflections on the ATOR 2019 - O'Sullivan, Michael (2019)
Michael O'Sullivan POLICY SEMINAR Gender Equality in Rural Africa: From Commitments to Outcomes Co-Organized by the Regional Strategic Analysis and Knowledge Support System (ReSAKSS) and IFPRI DEC 12, 2019 - 12:15 PM TO 01:45 PM EST